Proses Pelarangan Kegiatan Front Pembela Islam sebagai Organisasi Masyarakat Tahun 2020 - Muhammad Rizky Harahap (Universitas Warmadewa, 2022)
The hard-line Islamic Defenders Front (FPI) faced pressures from the government and public since the celebrated return of Rizieq Shihab, its so-called grand mufti, from exile in Saudi Arabia in November 2020. FPI elites had narrated the return of Shihab to lead the so-called â€œmorale revolution,â€ which arguably alerted security officials due to its seemingly radical choice of words. This article will examine how the issues surrounding FPI after its leaderâ€™s return were handled as security problems, which enabled measures outside normal political procedures. Drawing on the theory of securitization, this writing argues that the government presented FPI as threats to ideology, public order, and health before moving to ban FPI as a mass organization. The method of causal process tracing (CPT) is employed to trace events leading up to FPI's dissolution as a causal process.